Silesian Identity and Its Globalization-Influenced Transformation - Sagan, Radosław (Studia Etnologiczne i Antropologiczne, 2014)
The article presents the results of research concerning the Silesian identity in Katowice. The results obtained allowed the point group of residents of the city, whose identity is subject to change strongest today. Spatial analysis of the data also identified areas similar to each other in terms of the perception of the individual elements of the Silesian identity. Distinguished: os. Witosa, Podlesie and Szopienice-Burowiec as neighborhoods where most residents are attached to the region and the regional identity is strongest.